Grammatical Errors on Students’ Writing of Recount Text - Yudha Suranta P Siregar; Natalia Widya Pasca Tarigan; Cindy Ika Mawarni; Christine Widyantari Br Simanjuntak; Alfian Tanjaya (Institut Penelitian Matematika, Komputer, Keperawatan, Pendidikan dan Ekonomi (IPM2KPE), 2019)
This research aims to classify and analyze students’ types and sources of errors in writing recount text using simple past tense. This research used descriptive qualitative research. Furthermore, researchers used a written test and chose the 2nd grade students of Senior High School and observed 20 students. It was found the students do all the types of errors. Selection errors was the most common types of errors with 94 or 44,98% of errors. The second was the omission errors with 56 or 26,79% of errors. The third was the addition errors with 43 or 20,57% of errors. Then the last was misordering errors with 16 or 07,66% of errors. Furthermore, the errors weren’t caused by Indonesian language’s system but the complexity of English language’s system. Moreover, the lack of students’ understandings of grammar was the cause of the errors. In this research, most of the students didn’t understand present and past form of the verbs. It can be concluded that students had difficulty in writing using properly grammar because the English language’s system. Keywords: error analysis, types of errors, sources of errors.